KATA SAPAAN BAHASA SUKU ANAK DALAM DESA BUKIT SUBAN KECAMATAN AIR HITAM KABUPATEN SAROLANGUN - Sainil Amral; Eka Sulistiani (Aksara: Jurnal Ilmiah Pendidikan Bahasa dan Sastra Indonesia, 2021)
This research aims to describe the form and function of the words of the Language of Suku Anak Dalam di Desa Bukit Suban Kecamatan Air Hitam Kabupaten Sarolangun. This research uses the qualitative descriptive method. The data in this study is in the form of oral speech about greetings used to greet the speaker community in daily communication in Suku Anak Dalam di Desa Bukit Suban Kecamatan Air Hitam Kabupaten Sarolangun. The results of this research are in the form of descriptions of kinship and non-kinship greeting forms. Thus it can be said that the form of the kinship of Bahasa Suku Anak Dalam Desa Bukit Suban Kecamatan Air Hitam Kabupaten Sarolangun there are several types, namely the word direct kinship greeting in sequence such as the word "Puyang Jenton" which means great-grandfather, the term direct kinship greeting is not sequential as the word "Kakok Betina" which means sister. The word kinship is not directly marital relationship like the greeting "Obe" which means wife. As for the form of non-kin kinship greetings of Suku Anak Dalam Desa Bukit Suban Kecamatan Air Hitam Kabupaten Sarolangun there are several types, namely non-kinship greetings in general society such as the greeting word "Jengki" which means greedy people, non-kinship greetings in the field of customs such as the greeting "Tumenggung" which means the head of customs, and non-kinship greetings in the area of religion such as the greeting "Ngebang" which means people who chant the adzan.  Keywords: greetings, Anak Dalam tribe